Gas Hydrate Combustion in Five Method of Combustion Organization - Sergey Y. Misyura; Andrey Yu. Manakov; Galina S. Nyashina; Olga S. Gaidukova; Vladimir S. Morozov; Sergey S. Skiba (Entropy, 2020)
Experiments on the dissociation of a mixed gas hydrate in various combustion methods are performed. The simultaneous influence of two determining parameters (the powder layer thickness and the external air velocity) on the efficiency of dissociation is studied. It has been shown that for the mixed hydrate, the dissociation rate under induction heating is 10–15 times higher than during the burning of a thick layer of powder, when the combustion is realized above the layer surface. The minimum temperature required for the initiation of combustion for different combustion methods was studied. As the height of the sample layer increases, the rate of dissociation decreases. The emissions of NOx and CO for the composite hydrate are higher than for methane hydrate at the same temperature in a muffle furnace. A comparison of harmful emissions during the combustion of gas hydrates with various types of coal fuels is presented. NOx concentration as a result of the combustion of gas hydrates is tens of times lower than when burning coal fuels. Increasing the temperature in the muffle furnace reduces the concentration of combustion products of gas hydrates.